Chemical stability and electrical properties of Nb doped BaCe 0.9Y 0.1O 3-δ as a high temperature proton conducting electrolyte for IT-SOFC - Radojković, A.; Žunić, M. [UNESP]; Savić, S. M.; Branković, G.; Branković, Z. (My University, 2013)
BaCe 0.9-xNb xY 0.1O 3-δ (where x=0, 0.01, 0.03 and 0.05) powders were synthesized by solid-state reaction to investigate the influence of Nb concentration on chemical stability and electrical properties of the sintered samples. The dense electrolyte pellets were formed from the powders after being uniaxially pressed and sintered at 1550 °C. The electrical conductivities determined by impedance measurements in temperature range of 550-750 °C in different atmospheres (dry argon and wet hydrogen) showed a decreasing trend with an increase of Nb content. For all samples higher conductivities were observed in the wet hydrogen than in dry argon atmosphere. The chemical stability was enhanced with increasing of Nb concentration. It was found that BaCe 0.87Nb 0.03Y 0.1O 3-δ is the optimal composition that satisfies the opposite demands for electrical conductivity and chemical stability, reaching 0.8×10 -2 S cm -1 in wet hydrogen at 650 °C compared to 1.01×10 -2 S cm -1 for undoped electrolyte. © 2012 Elsevier Ltd and Techna Group S.r.l.
Keywords: C. Ionic conductivity; D. Perovskites; E. Fuel cells; Argon atmospheres; E. fuel cells; Electrical conductivity; High temperature; Impedance measurement; IT-SOFCs; Optimal composition; Proton-conducting electrolyte; Sintered samples; Temperature range; Electric conductivity; Electrolytes; Hydrogen; Perovskite; Powders; Sintering; Solid state reactions; Chemical stability